Short- and long-term cold storage of jack pine bolts is associated with higher concentrations of monoterpenes and nutrients ... - Guevara-Rozo, Sydne; Classens, Gail; Hussain, Altaf; Erbilgin, Nadir (University of Alberta Library, 2019)
Studies with conifer-infesting bark beetles commonly use bolts cut from trees to evaluate the effects of host tree quality on various aspects of insect biology. Yet, whether host quality changes between live trees and bolts cut from these trees has not been assessed. Particularly, changes in concentrations of defense chemicals (such as monoterpenes) and nutrients (such as nitrogen and carbon) have not been compared between live trees and their cut bolts. To determine whether monoterpene and nutrient concentrations differ after cutting, jack pine (Pinus banksiana Lamb.) trees in Lac La Biche (Alberta) were selected and sampled for phloem tissue. Then, these trees were harvested into two bolts per tree and stored at 4 °C for 3 and 6 months. Phloem was sampled from both live trees and bolts 3 and 6 months after storage. We found that major monoterpenes of jack pine were higher in phloem from bolts than from live trees. Storage time did not affect the results. Furthermore, some nutrients including nitrogen were ...